The Effect of BioDigital Human Augmented Reality on Elementary Students Learning Outcomes in Hearing System Topics - Putri Fatikasari; Miratu Chaeroh; Ririn Setyowati (BASICA, 2026)
This study aimed to examine the effect of BioDigital Human-based Augmented Reality (AR) learning media on science (IPAS) learning outcomes regarding the hearing sense among fifth-grade students at MI GUPPI Ngancar. The study employed a quantitative quasi-experimental approach using a nonequivalent control group design involving 52 students, consisting of an experimental group (n = 26) and a control group (n = 26). Data were collected through a validated and reliable multiple-choice achievement test and analyzed using N-Gain and Mann–Whitney U tests. The results indicated that students who learned using BioDigital Human-based AR achieved a higher mean posttest score (M = 73.08, SD = 11.75) than those who received conventional instruction (M = 59.04, SD = 14.86). The experimental group also demonstrated a greater increase in learning outcomes (+21.15 points) compared with the control group (+8.85 points), with a moderate N-Gain score (g = 0.44) versus a low N-Gain score in the control group (g = 0.18). Furthermore, the Mann–Whitney U test revealed a statistically significant difference between the two groups (U = 172.000, Z = −3.062, p = 0.002), with a moderate effect size (r = 0.42), classified as medium, confirming that the observed effect is not merely statiscally significant but also indicating a meaningful educational impact with genuine practical relevance for classroom practice. These findings suggest that BioDigital Human-based AR learning media effectively enhances students’ understanding of the hearing sense topic by facilitating interactive visualization of abstract anatomical concepts. Therefore, AR can be considered a promising instructional innovation for improving learning outcomes in primary science education, particularly for topics that are difficult to observe directly.